2014
DOI: 10.1038/hr.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of small dense low-density lipoprotein cholesterol associated with hemorheological abnormalities in untreated, early-stage essential hypertensives

Abstract: Among subfractions of low-density lipoprotein cholesterol (LDL-C), small dense LDL-C (SdLDL-C) has been highlighted as the most atherogenic lipoprotein cholesterol. The present study aimed to compare the relationship of SdLDL-C with blood viscosity, a surrogate marker for cardiovascular disease, with that of other lipid fractions with blood viscosity in essential hypertensives (EHTs). In 128 untreated, early-stage EHTs, blood viscosity was measured with a falling-ball microviscometer, and serum levels of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…A previous study revealed that blood viscosity correlated to diastolic blood pressure [29]. Similarly, in this study we found that all the hemorheological indices (including whole blood viscosity at various shear rates, plasma viscosity and erythrocyte rheology) were significantly related to diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 60%
“…A previous study revealed that blood viscosity correlated to diastolic blood pressure [29]. Similarly, in this study we found that all the hemorheological indices (including whole blood viscosity at various shear rates, plasma viscosity and erythrocyte rheology) were significantly related to diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 60%
“… 9 , 10 During the past decades, the relationship between hypertension and LDL subfractions, especially with the small dense LDL or the particle size, has been reported by multiple clinical studies. 11 13 It has, hence, suggested that hypertension may contribute to atherosclerosis with associated risk factors that influence LDL subfractions and particle size. In fact, HDL particle is more heterogeneous in its size and composition than LDL.…”
Section: Introductionmentioning
confidence: 99%
“…Blood viscosity, indeed, has been reported to be strongly predictive of cardiovascular events, and is a major risk factor for atherosclerosis. 23,24 It is also positively associated with high levels of LDL-C and hyperfibrinogenaemia. 23 In our patients, H.E.L.P.…”
Section: Discussionmentioning
confidence: 99%